Analisis Pengaruh Peralatan Bongkar Muat, Waktu Tunggu Truck , Kinerja Operator Bongkar Muat, Dan Tenaga Kerja (TKBM) Terhadap Produktivitas Bongkar Muat Batubara Di Pelabuhan Cirebon : Studi Kasus Pada PT. Bira Bumi Persada - Adenanthera Lesmana Dewa; Uut Dwi Karningsih; Retno Mulatsih (Journal Of Business, Finance, and Economics (JBFE), 2021)
Productivity of loading and unloading is one of the problems that always gets serious attention in every country, especially regarding sea transportation. Sea transportation is a meeting point for areas that are far from the center of activity, especially in supporting economic activities. with the port, economic activities canbecome smoother, most of the export and import goods are sent by sea because the number of goods that can be transported by ships is more than the number of goods that can be transported by other fleets. if the port's performance is less than optimal, it will have a direct impact on revenue so that it will cause new problems,namely a decrease in loading and unloading productivity. This study, Coal Loading and Unloading Productivity is influenced by several factors including loading and unloading equipment, truck waiting time, loading and unloading operator performance, and labor (TKBM) from these four factors which have an important role in increasing loading and unloading productivity. The population in this study were employees/employees and TKBM and service users at PT. Bira Bumi Persada with a research sample of 60 respondents. The data analysis used in this study was descriptive analysis and quantitative analysis, the data were analyzed using multiple linear regression analysis with the help of (software) Statistical Package For Social Science (SPSS) version.26. The results of the research by partially testing the t-test hypothesis showed that loading and unloading equipment, truck waiting time, loading and unloading operator performance, and labor (TKBM) had a positive and significant effect on coal loading and unloading productivity.